A Novel and Rapid Smear Cytomorphology Detection Strategy Based on Upconversion Nanoparticles Immunolabeling Integrated with Wright’s Staining for Accurate Diagnosis of Leukemia - Chen L; Zhong Y; Li YS; Zhuang H; Li X; Liu SP; Li JG; Lin Q; Gao F (International Journal of Nanomedicine, 2023)
Lu Chen,1,* Yu Zhong,2,* Yong-Sheng Li,3 He Zhuang,4 Xin Li,5 Sheng-Ping Liu,5 Jing-Gang Li,5 Qiu Lin,4 Fei Gao5 1Department of Paediatrics, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics and Gynecology and Pediatrics, Fujian Medical University, Fuzhou, 350000, People’s Republic of China; 2Department of Pharmaceutical Analysis, Faculty of Pharmacy, Fujian Medical University, Fuzhou, 350122, People’s Republic of China; 3Department of Urology, Fujian Medical University Union Hospital, Fuzhou, 350001, People’s Republic of China; 4Department of Clinical Laboratory, Fujian Medical University Union Hospital, Fuzhou, 350001, People’s Republic of China; 5Fujian Institute of Hematology, Fujian Provincial Key Laboratory on Hematology, Fujian Medical University Union Hospital, Fuzhou, 350001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei Gao, Email xuzhougaofei@126.comBackground: Accurate, sensitive, and rapid identification of leukemia cells in blood and bone marrow is of paramount significance for clinical diagnosis. An integrative technique combining traditional cytomorphology with immunophenotyping was proposed to improve the diagnostic efficiency in leukemia. On account of high photostability, biocompatibility, and signal-to-background ratio, upconversion nanoparticles (UCNPs) as luminescent labels have drawn substantial research scrutiny in immunolabeling.Methods: To achieve simultaneous determination, NaYF4:Yb,Er UCNPs were coupled with CD38 antibodies to construct immunofluorescence probes that were developed to bind to diffuse large B cell lymphoma (DLBCL) cells, followed by Wright’s staining that has been widely used in clinical work for morphological diagnosis. Further, the experimental conditions were optimized, such as medium, slice-making method, antibody dosage, incubation time, etc.Results: The cell morphology and immunolabeling could be observed simultaneously, and its simple operation rendered it a possibility for clinical diagnosis. The developed immunolabeling assay could achieve DLBCL cell counting with high reproducibility and stability, and the detection limit was as low as 1.54 cell/slice (> 3 σ/s). Moreover, the proposed method also realized real blood and bone marrow sample analysis, and the results were consistent with the clinical diagnosis.Conclusion: Overall, this strategy can be carried out after simple laboratory training and has prospective biomedical applications in leukemia classification, diagnosis validation, and differential diagnostics.Graphical Abstract: Keywords: leukemia, upconversion nanoparticle, immunofluorescence probe, Wright’s staining, cytomorphology